Alteration of Blood Oxidative Stress Status in Patients with Thoracic Aortic Dissection: A Pilot Study - Joël Pincemail; Vincent Tchana-Sato; Audrey Courtois; Lucia Musumeci; Jean-Paul C; Jacobine Munten; Nicos Labropoulos; Jean-Olivier Defraigne; Natzi Sakalihasan (MDPI AG, 2023)
Background: Thoracic aortic dissection (TAD) is a life-threatening condition which usually occurs on an aneurysmal aortic wall. Although increasing data have shown that inflammation and oxidative stress play an important role in the patho-physiology of dissection, systemic oxidative stress status (OSS) has not been clearly determined in patients suffering from TAD. Methods: A cohort of 115 patients presenting type A or B TAD were admitted to our center from 2013 to 2017. Out of this cohort, 46 patients were included in a study on dissected aorta (LIege study on DIssected Aorta: LIDIA). In 18 out of the 46 patients, systemic OSS parameters were evaluated after TAD diagnosis by determination of eight different antioxidants, four trace elements, two markers of oxidative lipid damage and two inflammatory markers. Results: The 18 TAD patients included 10 men and 8 women (median age: 62 years; interquartile range: 55-68) diagnosed with type A (N = 8) or B (N = 10) TAD. Low plasma levels of vitamin C, β-carotene, γ-tocopherol, thiol proteins, paraoxonase and selenium were observed in these 18 patients. By contrast, the concentration of copper and total hydroperoxides, copper/zinc ratio, as well as inflammatory markers, were higher than the reference intervals. No difference was observed in oxidative stress biomarker concentrations between type A and B TAD patients. Conclusions: This pilot study, limited to 18 TAD patients, revealed a heightened systemic OSS, determined at 15.5 days (median) after the initial diagnosis, in those TAD patients without complications (malperfusion syndrome and aneurysm formation). Larger studies on biological fluids are needed to better characterize the oxidative stress and interpret its consequence in TAD disease.